Wage Dips and Drops around First Birth - Astrid Kunze; Mette Ejrnaes (Institute for the Study of Labor (IZA), 2004)
We use a rich longitudinal data set for West Germany to disentangle the wage effects for female workers around first birth. Data on daily real wages reveal a dip in women's real wages shortly before giving birth and a drop of 10 to 20 percent after finishing maternity leave and returning to the labour market. To pinpoint what drives the movement in wages around the first birth, we analyse the wages of women, taking into account the potential correlation of the duration of individual interruptions due to parental leave with other unobserved individually specific factors and non random sample selection. In order to identify the causes of the movements in wages we exploit the panel structure of the data, regional variations in access to child care and female unemployment rates, as well as policy changes, which increased the maximum duration of parental leave from 6 months to 3 years.
Keywords: C23; J31; J13; 330; female wages; panel data; instrumental variable estimation; Frauenarbeitslohn; Mütter; Schätzung; Deutschland